RANCANG BANGUN SISTEM PENDETEKSI GERAK BERBASIS WEB DENGAN MENGGUNAKAN METODE FRAME DIFFERENCES DAN DYNAMIC TEMPLATE MATCHING - , MUHAMMAD IHSAN ZUL, Widyawan, S.T., M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Internet is one of technology that is used for various purposes. Internet is used to support business processes, education, information, social networking, and even for security systems are installed in offices, homes, and buildings. About the security system, camera is a device commonly used for monitoring in the case of security system. IP Camera is one of the devices commonly used to do surveillance with Internet. This research proposed the design of home surveillance system that uses the Internet. The system has been equipped with the ability to detect motion and web service as a means of system interoperability. Design of the system will be started from a review of home networking, design of web based IP Camera management system, motion detection algorithm, and web services. The method utilised for motion detection is frame differences and dynamic template matching. Furthermore, this research does the modification of dynamic template matching method to enhance the system. The method termed as dynamic and adaptive template matching (DATM). This research successfully completed a web-based home surveillance system that is equipped with motion detection system and the web service. The system is called by iHome. IHome works by using several tools including: IP Camera